2007
DOI: 10.1186/1745-0179-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundSeveral patients with unipolar depression present with prominent dysphoric mood. We aimed at examining the effectiveness of the combination of an SSRI with an anticonvulsant in such patients.MethodsThirty-five newly admitted outpatients with substantial anger, irritability, aggressiveness or hostility who were diagnosed a DSM-IV unipolar depressive disorder were rated on the Hamilton Depression Rating Scale (HDRS), the Clinical Global Improvement (CGI) scale, and a scale for the rapid dimensional ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…A few studies have examined the relationship between aging migrants and their social networks and have found that ethnicity and culture, such as differences in values and norms regarding social networks, can influence relationships with kin and non-kin of aging immigrants (Chappell 2003 ; Dalgard and Thapa 2007 ; Lai et al 2007 ; Mitchell 2003 ; Rao et al 2006 ; Slonim-Nevo et al 2009 ). Although kin relationships might be important for all older adults, immigrant adults originating from collectivistic countries might be especially prone to have close family ties that provide (instrumental) support and may alleviate loneliness (Johnson and Mullins 1987 ; Litwin 1997 ; Sánchez et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the relationship between aging migrants and their social networks and have found that ethnicity and culture, such as differences in values and norms regarding social networks, can influence relationships with kin and non-kin of aging immigrants (Chappell 2003 ; Dalgard and Thapa 2007 ; Lai et al 2007 ; Mitchell 2003 ; Rao et al 2006 ; Slonim-Nevo et al 2009 ). Although kin relationships might be important for all older adults, immigrant adults originating from collectivistic countries might be especially prone to have close family ties that provide (instrumental) support and may alleviate loneliness (Johnson and Mullins 1987 ; Litwin 1997 ; Sánchez et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diazepam use is common in patients having BPSD symptoms [ 56 ], but usage of diazepam together with citalopram can increase the risk of side effects and may contribute to fatal poisoning [ 57 ]. In comparison, valproate can be effective in treating aggression and behavioural activation related symptoms [ 58 ], and its combination with citalopram has proven to be effective, especially in depressed patients with dysphoric mood [ 58 ]…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее эффективными представ ляются психофармакологические стратегии, учи тывающие биологические механизмы, лежащие в основе патологических проявлений раздражитель ности и гнева, а также психотерапевтические ме тоды, обеспечивающие улучшение контроля над ними. [19,27,50]. Согласно данным кокрановского обзора [28] эффективность 4 антиэпилептических препара тов (вальпроат/дивалпроекс, карбамазепин, окскарбазепин и фенитоин) в отношении агрессии оценивается как противоречивая, что обусловли вает необходимость дальнейших исследований в этом направлении.…”
Section: заключениеunclassified